Low-carbon ecological oyster breeding cement substratum and preparation method thereof
By using carbonate gelling materials and specific additives, the problems of high carbon emissions, poor durability and low induction efficiency in the prior art are solved, and the preparation of low carbon, low alkalinity and high induction efficiency are achieved, which is suitable for oyster seedling cultivation.
Patent Information
- Application Number
- CN202311111135.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
The existing cement-based oyster attachment groups have problems such as high carbon emissions, poor durability, low induction efficiency and difficulty in preparing small thin sheets.
The ratio of carbonate cementitious materials, sand and water, combined with mineral blends, chopped fibers, dark pigments and calcium carbonate powder, low-carbon ecological oyster seedling cement adhesion substrate is prepared, and the alkalinity and performance of the adhesion substrate are regulated through specific maintenance processes, such as low-concentration carbon dioxide maintenance.
The cement-based adhesion group with low carbon, low alkalinity and high induction efficiency can effectively induce oyster adhesion, and the prepared adhesion base is easy to prepare small thin sheets and is suitable for oyster seedling cultivation.
Smart Images

Figure CN119522860A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the cross-technical field of aquatic product breeding and cement-based materials, and specifically relates to a low-carbon ecological oyster seedling cement attachment base and a preparation method thereof. Background Art
[0002] As people's living standards improve, the demand for nutritious and healthy food continues to increase. As a healthy food with a high cost-effectiveness, oysters are increasingly in demand. Common breeding methods include bamboo planting, bottom seeding, strip stone and standing stone breeding, and hanging breeding. However, the problem is that it takes a long time for oysters to achieve a satisfactory attachment rate on the attachment base, so it is necessary to first carry out artificial attachment in the nursery before breeding. However, due to the increase in the amount of oysters, the oyster attachment base of shellfish such as scallop shells can no longer meet the needs of oyster seedling cultivation, resulting in rising prices of shellfish attachment bases and regional imbalances in supply and demand. In addition, in the CN106719186 patent recently invented by the Ocean University of China: a new type of oyster attachment base is prepared by adding 15% to 20% of the mass of cement slurry shell powder and 5% to 15% of shell crushed shells. The shell crushed shells make the surface of the attachment base rough, increase the amount of oyster attachment, and have easier seed collection than scallop shells and better attachment effect. However, since water reducing agent is not considered for water consumption control and maintenance, and water-cement ratio and maintenance determine the permeability of cement-based materials, a large amount of alkali contained in the attachment base can be released, resulting in an increase in the alkalinity of the seawater in contact, inhibiting the attachment of marine fixed organism larvae, especially when raising seedlings in the nursery pond, the pH value of the water body may increase too much due to the small water body, resulting in the death of oyster larvae; at the same time, the large amount of shell powder added causes the color of the cement attachment base to change from dark gray to light, which is not conducive to the attachment of oysters.
[0003] In the patent CN 111268961 B invented by Lv Jianfu and others of Harbin Engineering, the cement dosage in the attachment base is reduced, the appropriate cement type is selected, and the cement with low alkalinity is obtained by adding appropriate mineral admixtures. At the same time, the water-cement ratio of the attachment base concrete is controlled, and its release rate is controlled. According to the attachment color preferred by oysters, biological calcium, calcium carbonate and trace elements are added to promote the early attachment, metamorphosis and later growth of oysters. However, there are problems such as high carbon emissions from the cement used, large size of the attachment base produced, and high concentration of carbon dioxide required during the curing process in order to reduce the alkalinity of the concrete.
[0004] Cement-based materials are easy to process, easy to attach seedlings, easy to remove, widely available and low-cost. However, there are still high carbon emissions and the raw materials are gradually becoming scarce. At the same time, the current oyster attachment bases with strong induction ability and good durability are all made into large-sized specimens, but in actual situations, we all need to use small thin slices for oyster seedling cultivation, especially many of the currently prepared cement attachment bases cannot be used immediately and require long-term soaking. Therefore, it is imperative to invent a low-carbon, low-alkalinity, high-induction efficiency cement attachment base to induce oyster attachment. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in two major types of concrete oyster basals: one type of oyster basal base has the problems of high cement consumption, poor concrete durability, and low efficiency in inducing oyster larvae to attach; the second type of concrete oyster basal base has good attachment efficiency and durability, but still has the problems of high carbon emissions and the presence of coarse aggregate, making it difficult to prepare an oyster basal base for seedling cultivation.
[0006] The invention provides a low-carbon ecological oyster seedling cement attachment base, which comprises the following components: carbonate cementitious material, sand and water, wherein the weight proportions of the carbonate cementitious material, sand and water are 15.0% to 58.8%, 29.0% to 71.0% and 3.8% to 28.6% respectively.
[0007] It is further defined that the carbonate cementitious material is carbonate mineral and water glass, and the weight ratio is 1:(0.08-0.3).
[0008] It is further defined that the carbonate mineral is one or more of calcite, dolomite, siderite, magnesite, smithsonite, aragonite, strontianite and cerussite.
[0009] It is further defined that the attachment base also includes mineral admixtures, and the mineral admixtures include one or more combinations of silica fume, slag and fly ash; the particle size of the mineral admixture is ≥200 mesh, and the weight ratio thereof is 0.75% to 18.4%.
[0010] Further defined, it also includes short-cut fibers or fiber sheets, wherein the short-cut fibers are short-cut fibers of 3-20 mm, and the volume addition amount is 0.2%-2.0% of the volume of the cementitious material; the mesh of the fiber sheet is 4mm2-400mm2, and the fiber cross-sectional size is 0.15mm 2 -12.56mm 2 .
[0011] It is further defined that it also includes one or more of calcium carbonate powder, biological calcium carbonate powder and dark pigment.
[0012] It is further defined that the biological calcium powder is oyster shell powder, egg shell powder, coral powder or fish bone; the weight ratio of the biological calcium is 0.5%-5.0%; the particle size of the biological calcium powder is ≥200 mesh; the calcium carbonate mineral powder is calcite, chalk, limestone, marble, aragonite, travertine powder; the weight ratio of the calcium carbonate powder is 0.5%-5.0%; the particle size of the calcium carbonate powder is ≥200 mesh.
[0013] It is further defined that the dark pigment is one or more of black iron oxide, aniline black, carbon black, antimony sulfide, red iron oxide, and organic pigment red, and the weight ratio of the dark pigment is 0.2%-2.0%.
[0014] The present invention provides a method for preparing a low-carbon ecological oyster seedling cement attachment base, comprising the following steps:
[0015] S1: Accurately weigh various raw materials;
[0016] S2: Pour various raw materials into the mixer and mix them thoroughly; after mixing evenly, pour and vibrate;
[0017] S3: Place the demoulding adhesion base specimens in a curing room with a temperature of 30-50°C and a humidity of ≥75% for curing for 3-14 days; then place the adhesion base specimens in a low-concentration carbon dioxide gas from industrial waste for curing for more than 8 hours to reduce the alkalinity of the adhesion base, thereby obtaining a low-carbon ecological oyster seedling cement adhesion base with good induction effect.
[0018] It is further defined that the low concentration of carbon dioxide gas is 5.0%-35.0%.
[0019] Beneficial effects: The present invention adopts carbonate cementitious materials, and mixes dark pigments and calcium carbonate materials, so that the prepared cement-based materials have strong ability to induce oyster attachment, and the attachment base material is easy to prepare a thin oyster attachment base with a diameter of 10 cm and a thickness of no more than 5 mm, which is not less than 1 cm compared to the minimum thickness of the attachment base on the market. At the same time, waste heat energy and direct use of solar energy for wet heat curing and low-concentration carbon dioxide curing are used, so that the attachment base mixed with fibers has good strength and anti-destruction ability, as well as lower alkalinity.
[0020] The present invention reduces carbon emissions by adopting carbonate cementitious materials, and at the same time utilizes waste gas emitted by power plants and other factories for maintenance to absorb the carbon dioxide therein, thereby further reducing carbon emissions. Under low concentrations of carbon dioxide, cement must ensure continued hydration and carbonization, which is a complex process. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1For the actual production of oyster substrate;
[0022] Figure 2 Soaking for attachment base;
[0023] Figure 3 To test the pH value of the substrate soaking solution. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below in conjunction with specific implementation modes.
[0025] These examples are only used to illustrate the present invention and do not limit the scope of the present invention. The implementation methods of Examples 1 to 16 are the same, and the mixing ratio of cement-based materials is as follows:
[0026] In the embodiment, the weight ratios of carbonate cementitious materials: dolomite powder (500 mesh) and water glass (based on sodium silicate solid, Na2O·nSiO2, n=1.5-3.5) are 90% and 10% respectively.
[0027] In the embodiment, 4 mm chopped fibers are used, and the volume content is 1.0%; the chopped fibers are one or more of basalt fibers, alkali-resistant glass fibers, synthetic fibers, and carbon fibers.
[0028] In the embodiment, the particle size of the mineral powder is 600-800 mesh and the particle size of the fly ash is 400-600 mesh.
[0029] In the embodiments, the calcium carbonate mineral powder is calcite, chalk, limestone, marble, aragonite, or travertine powder.
[0030] The particle size of the calcium carbonate powder in the embodiment is ≥200 mesh.
[0031] In the embodiment, the particle size of the biological calcium powder is ≥200 mesh, and the biological calcium powder is oyster shell powder, egg shell powder, coral powder or fish bone.
[0032] In the examples, nigrosine (CAS No. 11099-03-9) is used.
[0033] The sand is one or more of river sand, machine-made sand (the parent rock is one of granite and basalt) or desalinated sea sand, with a particle size range of 0.16mm-5.0mm and good gradation. The water should meet the concrete water standard (JGJ63-2006), Cl- content <1000mg / L, pH value >4.5. The water has little effect on the initial setting time difference and final setting time, strength and permeability of cement. The above materials selected in Examples 1 to 16 are the same.
[0034] Embodiment 1:
[0035] The weight ratios of the benchmark cement-based material mix, carbonate binder, sand and water are 25.6%, 64.1% and 11.3% respectively.
[0036] The sand is one or more of river sand, machine-made sand (the parent rock is one of granite and basalt) or desalinated sea sand, with a particle size range of 0.16mm-5.0mm and good gradation. The water should meet the concrete water standard (JGJ63-2006), Cl- content <1000mg / L, pH value >4.5. The water has little effect on the initial setting time difference and final setting time, strength and permeability of cement. The above materials selected in Examples 1 to 16 are the same.
[0037] Embodiment 2:
[0038] The mix ratio of cement-based materials with added fibers: the weight ratios of carbonate cementitious materials, sand, chopped fibers and water are 25.5%, 63.8%, 0.45% and 11.25% respectively.
[0039] Embodiment 3:
[0040] The weight ratios of cement-based materials, carbonate cementitious materials, sand and water are 15.0%, 71.0% and 14.0% respectively.
[0041] Embodiment 4:
[0042] The weight proportions of cement-based materials, carbonate cementitious materials, sand and water are 50.0%, 29.0% and 21.0% respectively.
[0043] Embodiment 5:
[0044] The weight ratios of slag powder, cement-based materials, slag powder, carbonate cementitious materials, sand, chopped fibers and water are 8%, 17.5%, 63.8%, 0.45% and 11.25% respectively.
[0045] Embodiment 6:
[0046] The mix ratio of fly ash cement-based materials is as follows: the weight ratios of fly ash, carbonate cementitious materials, sand and water are 3.0%, 22.6%, 64.1% and 11.3% respectively.
[0047] The particle size of mineral powder is 600 mesh-800m and the particle size of fly ash ranges from 400 mesh-600 mesh.
[0048] Table 1
[0049]
[0050] Embodiment 7:
[0051] The weight proportions of aniline black (CAS No. 11099-03-9), mineral powder, carbonate cementitious material, sand and water are 0.3%, 8.0%, 17.6%, 63.8% and 11.3% respectively.
[0052] Embodiment 8:
[0053] The weight proportions of aniline black, mineral powder, carbonate cementitious material, sand and water are 0.4%, 8.0%, 17.6%, 63.7% and 11.3% respectively.
[0054] Embodiment 9:
[0055] The weight proportions of aniline black, mineral powder, carbonate cementitious material, sand and water are 0.5%, 8.0%, 17.6%, 63.6% and 11.3% respectively.
[0056] Table 2
[0057]
[0058] Embodiment 10:
[0059] The weight proportions of oyster shell powder, mineral powder, carbonate cementitious material, sand and water are 0.5%, 7.5%, 17.6%, 64.1% and 11.3% respectively.
[0060] Embodiment 11:
[0061] The weight proportions of oyster shell powder, mineral powder, carbonate cementitious material, sand and water are 1.0%, 7.0%, 17.6%, 64.1% and 11.3% respectively.
[0062] Embodiment 12:
[0063] The weight proportions of oyster shell powder, mineral powder, carbonate cementitious material, sand and water are 1.5%, 6.5%, 17.6%, 64.1% and 11.3% respectively.
[0064] Embodiment 13:
[0065] The weight proportions of calcium carbonate powder, mineral powder, carbonate cementitious material, sand and water are 0.5%, 7.5%, 17.6%, 64.1% and 11.3% respectively.
[0066] Embodiment 14:
[0067] The weight proportions of calcium carbonate powder, mineral powder, carbonate cementitious material, sand and water are 1.0%, 7.0%, 17.6%, 64.1% and 11.3% respectively.
[0068] Embodiment 15:
[0069] The weight proportions of calcium carbonate powder, mineral powder, carbonate cementitious material, sand and water are 1.5%, 6.5%, 17.6%, 64.1% and 11.3% respectively.
[0070] Embodiment 16:
[0071] The weight proportions of oyster shell powder, aniline black, mineral powder, carbonate cementitious material, sand and water are 1.0%, 0.5%, 7.0%, 17.6%, 63.6% and 11.3% respectively.
[0072] The particle size of oyster shell powder is 400-600 mesh, and the particle size of calcium carbonate powder is 600 mesh-800 mesh.
[0073] Table 3
[0074]
[0075] Example 17. A method for preparing a low-carbon ecological oyster seedling cement attachment base
[0076] S1: Accurately weigh various raw materials (according to Example 2);
[0077] S2: Pour various raw materials into the mixer and mix them thoroughly; after mixing evenly, pour and vibrate;
[0078] S3: Place the demoulding adhesion base specimens in a curing room with a temperature of 30-50°C and a humidity of ≥75% for curing (using waste heat or directly using solar energy) for 3-14 days; then place the adhesion base specimens in 12% carbon dioxide gas from industrial waste for curing for more than 8 hours to reduce the alkalinity of the adhesion base, and a low-carbon ecological oyster seedling cement adhesion base with good induction effect can be obtained, with a compressive strength greater than 40MPa. The prepared adhesion base can withstand no less than 5 drops from a height of 2m, and the alkalinity of the adhesion base is lower than 8.0. Figure 1 For the actual production of oyster substrate; Figure 2 Soak the substrate. Figure 3 To test the pH value of the substrate soaking solution.
[0079] The specific operation steps of the implementation method of embodiments 1 to 17 are as follows:
[0080] (I) Specimen Forming
[0081] 1. Calculate and accurately weigh the raw materials according to the above mass.
[0082] 2. Stir the mixture until it is evenly mixed, and then make three Φ100×50mm cylindrical specimens, a 100mm cubic specimen, and ten round cake specimens with a diameter of 10cm and a thickness of 5mm. Finally, place them in a standard curing room for 28 days before conducting laboratory experiments on oyster larvae attachment and metamorphosis.
[0083] (II) The specific steps of water absorption test are as follows:
[0084] (1) When the standard curing age of the specimen reaches 28 days, take the specimen out of the curing room.
[0085] (2) Place the specimen in a vacuum drying oven to dry, then apply a layer of epoxy resin on its side surface. After the epoxy resin is cured, stick a layer of aluminum foil on the molding surface of the specimen. The purpose is to prevent external moisture from entering the interior through the side and molding surface of the specimen.
[0086] (3) Pour a certain amount of water into the iron plate at the bottom of the FRP bar, so that it covers the FRP bar by about 1 mm to 2 mm. Then place the sealed specimen on the FRP bar of the iron plate to ensure that the specimen can only absorb water from the bottom into the concrete through capillary absorption.
[0087] (4) During the test, take 0.1 2 , 0.2 2 , 0.3 2 , 0.4 2 , 0.6 2 , 0.8 2 , …, 2.8 2 To measure the time point, take out the specimen at the corresponding measuring time point, wipe off the excess moisture with a rag, weigh and record its mass. For each data point, take the average of the test values of three specimens with the same mix ratio and the same age.
[0088] The formula for water absorption is:
[0089] ΔW is the water absorption per unit area of the sample, k is the water absorption coefficient, and t is the test time
[0090] (III) The specific steps of the indoor oyster larvae attachment and metamorphosis experiment are as follows:
[0091] After 28 days of standard curing, round cake specimens with a diameter of 10 cm and a thickness of 5 mm were taken out from the curing room, the moisture and debris on the surface of the specimens were cleaned, and then they were placed in the seawater test pool, and the oyster larvae were evenly spread in the test pool. Then, the seed attachment experiment was carried out. After the experiment lasted for 30 days, the water in the test pool was drained, the specimens were taken out, and the number of oysters on the surface of the specimens and the survival rate were statistically recorded and analyzed.
[0092] The formula for the attachment rate of oyster larvae per unit area is y=1200+aX1+bX2, where a is a constant term ranging from 8 to 30, b is a constant term ranging from 400 to 2000, X1 is the dosage of carbonate mineral powder, and X2 is the dosage of inducer.
[0093] Compared with the reference document 1 (a rough surface cement concrete oyster attachment base and preparation method CN111268961 B), the difference is:
[0094] Comparative Document 1 uses a cementitious material which is a silicate cement added with mineral admixtures, one of sulphoaluminate cement and alkali-activated cementitious material; wherein the mineral admixtures in the silicate cement added with mineral admixtures include one or more combinations of silica fume, slag powder and fly ash; sulphoaluminate cement includes one or two of fast-hardening sulphoaluminate cement, high-strength sulphoaluminate cement and expansive sulphoaluminate cement; and the alkali-activated cementitious material includes one of alkali-activated slag and alkali-activated slag + fly ash.
[0095] The present invention adopts carbonate cementitious materials, and appropriately adds slag powder, fly ash and kaolin powder for modification, which has the characteristics of low-carbon ecology, and carbonate minerals are very abundant in the case of increasingly depleted limestone resources. In addition, since carbonate cementitious materials themselves contain more calcium substances, the problem that must be solved in the present invention is to control the calcium carbonate content in the cement attachment base through the design of raw material ratio, the control of temperature and humidity for curing, and the control of the concentration and time of carbon dioxide curing.
[0096] Compared with reference document 2 (a new type of concrete artificial fish reef and its preparation method CN104529286 A), the difference is:
[0097] The purpose of the present invention is different from that of the reference document: although reference document 2 adds oyster shell powder into concrete, its purpose is to utilize waste and repair and improve artificial reefs. The purpose of the present invention is to induce the attachment of oyster larvae.
[0098] Compared with reference document 3 (an oyster attachment base for silicate cement concrete and preparation method CN 111268957 B), the difference is:
[0099] Comparative Document 3, the cementitious materials used are silicate cement and mineral admixtures. In the present invention, carbonate cementitious materials are used, and slag powder, fly ash and kaolin powder are appropriately added for modification, which has the characteristics of low-carbon ecology, and carbonate minerals are very abundant in the case of increasingly depleted limestone resources. Although dark pigments and calcium carbonate powder are used as substances to induce oysters, carbonate cementitious materials themselves contain more calcium substances, and calcium carbonate substances will also be hydrated during the hydration process. Therefore, the problems that must be solved in the present invention are to control the calcium carbonate content in the cement attachment base through the design of raw material proportions, control of temperature and humidity for maintenance, and control of the concentration and time of carbon dioxide maintenance, and to induce the attachment of oysters, but the comparative documents do not have such problems.
[0100] Therefore, since this part of knowledge involves the intersection of marine fixed organisms, marine chemistry and cement-based materials, technicians in the fields of cement-based materials, marine engineering or marine biology cannot obtain the technical features of the carbonate cementitious material in the present invention that is closely related to the permeability of the cement-based material after adding dark pigments and calcium carbonate materials, and the carbonate cementitious material cooperates with the dark pigment to improve the ability to induce oyster attachment through reference document 1. And they cannot obtain the hydration of carbonate in the present invention and the high efficiency of hydration products inducing oyster attachment through reference document 3.
[0101] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low-carbon ecological oyster seedling cement attachment base, characterized in that: The attachment base comprises the following components: carbonate cementitious material, sand and water, wherein the weight proportions of the carbonate cementitious material, sand and water are 15.0% to 58.8%, 29.0% to 71.0% and 3.8% to 28.6% in sequence.
2. The low-carbon ecological oyster seedling cement attachment base according to claim 1, characterized in that: The carbonate cementitious material is composed of carbonate minerals and water glass, with a weight ratio of 1:(0.08-0.3).
3. The low-carbon ecological oyster seedling cement attachment base according to claim 2 is characterized in that: The carbonate mineral is one or more of calcite, dolomite, siderite, magnesite, smithsonite, aragonite, strontianite and cerussite.
4. The low-carbon ecological oyster seedling cement attachment base according to claim 1, characterized in that: It also includes mineral admixtures, which include one or more combinations of silica fume, slag and fly ash; the particle size of the mineral admixture is ≥200 meshes, and the weight ratio thereof is 0.75% to 18.4%.
5. The low-carbon ecological oyster seedling cement attachment base according to claim 1, characterized in that: It also includes chopped fibers or fiber sheets, wherein the chopped fibers are 3-20 mm chopped fibers, and the volume content is 0.2%-2.0% of the volume of the cementitious material; the mesh of the fiber sheet is 4 mm 2 -400mm 2 , fiber cross-section size 0.15mm 2 -12.56mm 2 .
6. The low-carbon ecological oyster seedling cement attachment base according to claim 1, characterized in that: It also includes one or more of calcium carbonate powder, biological calcium carbonate powder and dark pigments.
7. The low-carbon ecological oyster seedling cement attachment base according to claim 6 is characterized in that: The biological calcium powder is oyster shell powder, egg shell powder, coral powder or fish bone; the weight ratio of the biological calcium is 0.5%-5.0%; the particle size of the biological calcium powder is ≥200 mesh; the calcium carbonate mineral powder is calcite, chalk, limestone, marble, aragonite, travertine powder; the weight ratio of the calcium carbonate powder is 0.5%-5.0%; the particle size of the calcium carbonate powder is ≥200 mesh.
8. The low-carbon ecological oyster seedling cement attachment base according to claim 6, characterized in that: The dark pigment is one or more of black iron oxide, aniline black, carbon black, antimony sulfide, red iron oxide, and organic pigment red, and the weight ratio of the dark pigment is 0.2%-2.0%.
9. A method for preparing a low-carbon ecological oyster seedling cement attachment base, characterized in that: The steps include: S1: Accurately weigh various raw materials; S2: Pour various raw materials into the mixer and mix them thoroughly; after mixing evenly, pour and vibrate; S3: Place the demoulding adhesion base specimens in a curing room with a temperature of 30-50°C and a humidity of ≥75% for curing for 3-14 days; then place the adhesion base specimens in a low-concentration carbon dioxide gas from industrial waste for curing for more than 8 hours to reduce the alkalinity of the adhesion base, thereby obtaining a low-carbon ecological oyster seedling cement adhesion base with good induction effect.
10. The preparation method according to claim 9, characterized in that: The low concentration of carbon dioxide gas is 5.0%-35.0%.
Citation Information
Patent Citations
Novel concrete artificial fish reef and preparation method thereof
CN104529286A
An oyster shell adhesion substrate for silicate cement concrete and its preparation method
CN111268957B
A rough-surfaced cement concrete oyster shell adhesion substrate and its preparation method
CN111268961B
Building material based on interaction of alkali and CO2
CN101381217A
Cement concrete oyster attachment substrate with rough surface and preparation method thereof
CN111268961A
Cited By
Monomer oyster seed attaching material and preparation method thereof
CN120982448A